COVID‐19 Disease Map, a computational knowledge repository of virus‐host interaction mechanisms. Issue 12 (23rd December 2021) - Ostaszewski, Marek; Niarakis, Anna; Mazein, Alexander; Kuperstein, Inna; Phair, Robert; Orta‐Resendiz, Aurelio; Singh, Vidisha; Aghamiri, Sara Sadat; Acencio, Marcio Luis; Glaab, Enrico; Ruepp, Andreas; Fobo, Gisela; et al.
Abstract :